A Bit on the Side - Trevor W. William (London, Penguin Books, 2004)
Tender, touching and beautifully humane, the dozen new stories contained here explore the subject of adultery, and tell of secret passions, domestic infidelities, office romances, and the broken and unbroken rules of love